Pooled estimate of vitamin D deficiency among pregnant women in India: a systematic review and meta-analysis - Angeline Jeyakumar; Vidhya Shinde; Reshma Ravindran (BMC, 2021)
Abstract Background Vitamin D deficiency among pregnant women is a public health concern globally. In India, individual studies report high prevalence. However, lack of national data masks the true burden. This work determined the pooled prevalence of vitamin D deficiency among pregnant women in India through a systematic review of literature and meta-analysis. Methods Three different search engines yielded 15 eligible articles. Study quality was assessed by 10 different criteria and summary of study quality was categorized as per Cochrane standards. Meta-analysis was performed to estimate pooled prevalence of vitamin D deficiency among healthy pregnant women and heterogeneity among selected studies. A sample of n = 4088 was used to study the pooled prevalence among pregnant women. Results The random effects combined estimate was 32.35% (95% CI, (12.58-117.48). High heterogeneity (tau2 = 0.39, I2 = 100%) and high risk of bias was observed among the selected studies. The test for overall effect was observed to be z = 2.54(P = 0.01). Conclusion Pooled estimate > 30% emphasizes the need for screening through antenatal care services and initiate preventive measures to address the deficiency.